2009
DOI: 10.1002/gps.2290
|View full text |Cite
|
Sign up to set email alerts
|

Anterior cingulate cortical volumes and treatment remission of geriatric depression

Abstract: SUMMARYBackground Structural abnormalities of the anterior cingulate cortex (ACC) may interfere with the interaction of cortical and limbic networks involved in emotional regulation and contribute to chronic depressive syndromes in the elderly. This study examined the relationship of regional anterior cingulate cortical volumes with treatment remission of elderly depressed patients. We hypothesized that patients who failed to remit during a 12-week controlled treatment trial of escitalopram would exhibit small… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
61
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 99 publications
(64 citation statements)
references
References 48 publications
3
61
0
Order By: Relevance
“…Although two studies associated a smaller right superior frontal gyrus with remitters (Costafreda et al, 2009;Li et al, 2010), Jung et al (2014) showed significantly smaller volumes in patients who did not respond to 8 weeks of ADM, compared to healthy controls (Jung et al, 2014). More consistent findings have been seen with the anterior and posterior cingulate cortices, with larger sizes of both structures predicting remission (Costafreda et al, 2009;Gunning et al, 2009;Jarnum et al, 2011). Although no more than 2 reviewed papers have corroborated these findings, a small number of ADM treatment response studies have provided further support for cingulate size (Chen et al, 2007;Samann et al, 2013).…”
Section: Structural Biomarkersmentioning
confidence: 76%
See 1 more Smart Citation
“…Although two studies associated a smaller right superior frontal gyrus with remitters (Costafreda et al, 2009;Li et al, 2010), Jung et al (2014) showed significantly smaller volumes in patients who did not respond to 8 weeks of ADM, compared to healthy controls (Jung et al, 2014). More consistent findings have been seen with the anterior and posterior cingulate cortices, with larger sizes of both structures predicting remission (Costafreda et al, 2009;Gunning et al, 2009;Jarnum et al, 2011). Although no more than 2 reviewed papers have corroborated these findings, a small number of ADM treatment response studies have provided further support for cingulate size (Chen et al, 2007;Samann et al, 2013).…”
Section: Structural Biomarkersmentioning
confidence: 76%
“…In these patients, larger dorsal and rostral ACC volumes were associated with remission (Gunning et al, 2009). A subsequent study showed significantly reduced PCC thickness in 9 patients who did not remit after 6 months of mixed ADM, compared with 8 remitters.…”
Section: Gm Volume and Cortical Thickness Measurementsmentioning
confidence: 88%
“…Reduced ACC volume was found to be associated with attention biases towards negative, depressionrelated cues (Leung et al, 2009), with a diminished ability to down-regulate negative -but not positive -emotions (Mak et al, 2009), with worse executive performance (Vasic et al, 2008), and with higher risk for suicidal behavior (Wagner et al, 2011). Lastly, ACC volume decrease was found to correlate with negative antidepressant treatment response in cross-sectional imaging studies of MDD (Chen et al, 2007;Gunning et al, 2009). …”
Section: Discussionmentioning
confidence: 88%
“…The functioning of the rostal ACC has been found to be altered due to depression, as shown by deviating ERP responses in depressed older adults following an emotional go-no/go paradigm [93]. Also, smaller gray matter volumes of the ACC correlated with poor effects of antidepressant treatment [96], indicating that preexisting conditions affecting the anterior cingulate may be one reason why many elderly depressed patients do not respond to common antidepressant treatments [18]. Reduced N2 components within ACC correlate with poorer performance on the inhibition control task, suggesting that depression causes less efficient processing within the ACC, or perhaps that brain plasticity has shifted inhibition control processing to less specialized areas [13] [18].…”
Section: Inhibition Controlmentioning
confidence: 99%